New approaches for health sector development collaboration in the Baltic Sea and Barents region - Arsalo, Ali; Vainiomäki, Paula (Stakes, 2003)
Sisältää kahden projektin arvioinnin: Project for Infectious Disease Control in the Barents and Baltic Sea Regions in 1998-2001 ja Promoting the Key Role of Family Medicine for Better Health (Report of the Primary Health Care Programme Group 2000-2004, Task Force on Communicable Disease Control in the Baltic Sea Region)